POLICY OF SUSTAINABILITY FOR INDONESIAN ROAD DEVELOPMENT - Murjanto, Djoko (Jurnal HPJI, 2015)
Abstract Road infrastructure performance in Indonesia is important, because almost 90% of businesses use the road infrastructure as a way of moving their products. Road Infrastructure itself is a backbone of passenger and good transport as further as economic development. Current challenge is developing policy of sustainable road development. Indonesia is commit to improve the effort in carbon emission reduction as high as 26% through business as usual with self-capability as stated by President Yudhoyono. Then it is followed by the issue of National Action Plan of Mitigation and Adaptation of Climate Change (RAN-MAPI) in road sector which is consist of two phase: (i) Long term RAN-MAPI (2012-2020), and (ii) Medium term RAN-MAPI 2012-2014. The development of vetiver grass and adoption of Asphalt Recycling Technology is the example of environmentally friendly effort related to the National Action Plan. In the end, the objective of Environment Management is to create environmentally sustainable development as planned effort in harmony with environment including resource for development process in order to achieve prosperity and better quality of life of the present and future development. Keywords: sustainable road, carbon emission, climate change, road development  Abstrak Kondisi Infrastruktur jalan sangat penting karena 90% usaha menggunakan jalan untuk angkutan produk-produk mereka. Jalan juga tulang punggung angkutan penumpang dan barang. Tantangan saat ini adalah pengembangan kebijakan jalan berkelanjutan. Indonesia sepakat untuk mereduksi emisi karbon hingga 26% melalui kegiatan rutin dengan kapabilitas yang dimiliki sesuai pernyataan Presiden Susilo Bambang Yudhoyono. Berikutnya, mengikuti kebijakan dari Rencana Aksi Nasional Mitigasi dan Adaptasi Perubahan Iklim (RAN-MAPI) untuk sektor jalan yang terdiri dari dua tahap: (i) Rencana Jangka Panjang RAN-MAPI (2012-2020) dan (ii) Rencana Jangka Menengah  RAN-MAPI (2012-2014). Pengembangan rumput vetiver dan teknologi adopsi daur ulang aspal  adalah contoh upaya ramah lingkungan berkaitan dengan Rencana Aksi Nasional. Di akhir makalah, tujuan dari manajemen lingkungan adalah untuk menciptakan pengembangan lingkungan berkelanjutan sesuai dengan upaya untuk menciptakan kelarasan lingkungan termasuk sumber daya dalam proses pengembangan untuk terciptanya kemakmuran dan kondisi kualitas lingkungan saat ini dan masa depan. Kata-kata kunci: jalan berkelanjutan, emisi karbon, perubahan iklim, pengembangan jalan